NEEDLE STICK INJURIES IN NURSES AT A TERTIARY HEALTH CARE FACILITY - Manzoor, Iram; Daud, Seema; Hashmi, Norren Rahat; Sardar, Hira; Babar, Mirza Shaharyar; Rahman, Abdul; Malik, Madiha (Journal of Ayub Medical College Abbottabad, 2010)
Background: Needle-stick injury (NSI) is a major occupational health and safety issue faced by healthcare professionals globally. This study was aimed to assess the frequency and factors associated with NSIs in nurses of a tertiary health care facility in Lahore, Pakistan. It also focuses on safety measures adopted by these nurses after a needle stick injury. Methods: This cross-sectional descriptive study was conducted in Ghurki Trust Teaching Hospital, Lahore from October 2009 to January 2010. All nurses have participated in the study with a response rate of 99%. These responses were obtained via a pretested self-administered questionnaire. The data was analysed using SPSS-16. Percentages of the categorical variables were computed and represented in various statistical data presentation forms, for analysis and comparison. Chi-square test was applied as a test of significance with fixing the pvalue of 0.05 as significant. Results: Out of 77 nurses who participated in our study, only 33 (42%) nurses were aware of the occupational hazards of their profession when they joined nursing. Needle stick injury was reported by 40 (71.9%) of the nurses in last one year. About 17 (31.5%) were injured at the time of recapping the syringe. The availability of needle cutters in the hospital was reported by 75 (97.4%) nurses while only 46 (60%) of them had undertaken a sharp management training course. Approximately 50 (64.9%) nurses failed to use gloves while administering injections. After getting stuck by a contaminated needle 71 (92%) of the nurses cleaned the wound with a spirit swab, 67 (87%) washed the area with soap and water and 58 (75%) applied a readily available bandage. Only 38 (49%) went on to inform the higher officials about a needle stick injury. Fifty-seven (74%) of the nurses were vaccinated against HBV, and 56 (72.2%) of needle stick injured nurses proceeded for HBV screening, while 53 (68.6%) for HCV and 37(48.5%) for HIV. Conclusion: Needle stick injury is the most important occupational health hazard in nurses with alarmingly high rates. Reporting to the concerned authorities, screening of nurses after needle stick injury and promotion of safety measures against it should be greatly encouraged. Keywords: Needle stick injuries, Nurses, Pakistan